Mast cell depletion in the preclinical phase of collagen-induced arthritis reduces clinical outcome by lowering the inflammatory cytokine profile. Issue 1 (December 2016) - van der Velden, Daniël; Lagraauw, H.; Wezel, Anouk; Launay, Pierre; Kuiper, Johan; Huizinga, Tom; Toes, René; Bot, Ilze; Stoop, Jeroen
Abstract Background Rheumatoid arthritis (RA) is a multifactorial autoimmune disease, which is characterized by inflammation of synovial joints leading to the destruction of cartilage and bone. Infiltrating mast cells can be found within the inflamed synovial tissue, however their role in disease pathogenesis is unclear. Therefore we have studied the role of mast cells during different phases of experimental arthritis. Methods We induced collagen-induced arthritis (CIA), the most frequently used animal model of arthritis, in an inducible mast cell knock-out mouse and determined the effect of mast cell depletion on the development and severity of arthritis. Results Depletion of mast cells in established arthritis did not affect clinical outcome. However, depletion of mast cells during the preclinical phase resulted in a significant reduction in arthritis. This reduction coincided with a decrease in circulating CD4+ T cells and inflammatory monocytes but not in the collagen-specific antibody levels. Mast cell depletion resulted in reduced levels of IL-6 and IL-17 in serum. Furthermore, stimulation of splenocytes from mast cell-depleted mice with collagen type II resulted in reduced levels of IL-17 and enhanced production of IL-10. Conclusions Here we show that mast cells contribute to the preclinical phase of CIA. Depletion of mast cells before disease onset resulted in an altered collagen-specific T cell and cytokine response. These data may suggest that mast cells play a role in the regulation of the adaptive immune response during the development of arthritis.